Wheel-rail impact at an insulated rail joint in an embedded rail system. (1st November 2021) - Yang, Zhen; Zhang, Pan; Wang, Li
Graphical abstract: Highlights: High-frequency dynamic responses of an embedded rail system (ERS) are reliably predicted. The FE wheel-rail impact model is rigorously validated with a hammer test and a train pass-by measurement. Geometric irregularities and train speeds determine the dominant frequencies of the impact vibration of rail joints in the ERS. The ERS is more impact-resistant than traditional tracks. Abstract: With dynamic behaviour different from that of traditional discretely supported tracks, continuously supported embedded rail systems (ERSs) have been increasingly used in railway bridges, level crossings, trams, and high-speed lines. However, studies on ERSs have been limited, and none of them have addressed the wheel-rail impact-induced dynamic response, although wheel-rail impact is a main cause of ERS degradation. This paper studies, numerically and experimentally, the wheel-rail impact at an insulated rail joint (IRJ) used in the ERS. As a weak spot of the track, the IRJ results in discontinuities in the track support stiffness and wheel-rail contact geometry. This study first develops an explicit finite element model to simulate the vibration responses of the IRJ in the ERS when excited by a hammer and passing wheel loads. The simulated dynamic behaviours (represented by the hammer-excitation frequency response function) at a frequency up to 5 kHz and a wheel-rail impact vibration frequency up to 10 kHz are then validated with a field hammer test and a train pass-by measurement, respectively. Both the experimental study and numerical modelling reveals that the major frequencies of the impact vibration at the IRJ in the ERS depend mainly on geometric irregularities in the IRJ region and the train speed, rather than on the resonances of the track structure, as in the case of the discretely supported IRJ. This finding is meaningful to the engineering practice because it indicates a continuously supported IRJ in the ERS is more impact resistant, especially when the IRJ geometry is adequately maintained, e.g. by timely grinding.